Kemampuan Pemodelan Matematika Siswa SMP Kelas VII Berbantuan E-LKPD Materi Operasi Bilangan Bulat - Muhammad, Bagas Al Faruq; Kurniadi, Elika (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to describe students' mathematical modeling abilities in learning integer operations assisted by E-LKPD, namely with Liveworksheets learning media. This study uses a qualitative descriptive research type with research subjects, namely 25 students of class VII.1 SMP Negeri 3 Tanjung Raja. Data were collected through tests and interviews. Data analysis is based on the results of each student's written test and interviews with students according to the predetermined category of mathematical modeling abilities. Students' mathematical modeling abilities are seen based on indicators of mathematical modeling abilities. The results of the study show that students' mathematical modeling abilities in learning assisted by Liveworksheets are categorized as very good with a percentage of 52%, categorized as good with a percentage as 24%, categorizes as sufficient with a percentage of 18%, and categorized as less with a percentage of 6%. In working on the test questions given by the researcher, most students can meet the indicators of mathematical modeling abilities well and are able to solve problems with correct answer conclusions. However, in the process of solving the problems, students still encountered obstacles such as errors in identifying the problem, creating an inappropriate mathematical model, not identifying variables correctly, and confusion and errors in the mathematical solution process. Although they made errors in some parts of the problem solving, overall, students were able to solve the problems given well.